From Rebellion to Reform: Representations of Regional and Civic Improvement in the Aberdeen Journal, 1747–85. Issue 2 (November 2021) - Benchimol, Alex
Abstract : The role of the Aberdeen Journal in facilitating the commercial modernization of Aberdeen and the northeast of Scotland in the four decades after the Battle of Culloden is an understudied aspect of the city's and region's social, economic and cultural history. This article examines the way improvement initiatives from key regional and civic stakeholders like the Board of Trustees for Fisheries, Manufactures and Improvements in Scotland, the Aberdeenshire Society for the Encouragement of Agriculture and Manufactures, the Commissioners of Supply, Aberdeen Town Council, and Marischal College were represented in the newspaper. In particular it highlights how James Chalmers 2 and James Chalmers 3—the Aberdeen Journal 's proprietors during its first forty years—developed Scotland's first newspaper north of Edinburgh as an informational hub to integrate the city and region into key currents of Scottish and British capitalist modernization in the second half of the eighteenth century, from linen manufacturing and processing, to land reform and agricultural improvement. The social and economic transformation facilitated by the newspaper led to demands for political reform by those new commercial stakeholders, like John Ewen and Patrick Barron, who had profited from this regional modernization, and the article argues that the Aberdeen burgh reform movement of the early 1780s that utilized the Aberdeen Journal as a principal periodical platform was an essential consequence of this trajectory of regional and civic improvement, and a key test for translating it into a tangible expansion of democratic rights.